Studi Sejarah Kebudayaan Islam Dari Zaman Rasulullah Saw, Khulafaur Rasyidin, Bani Umayyah Dan Bani Abassiyah - Jasmina Syafe'i; Nadia Putri; Sahbila Aura; Zeni Mahmuda; Delmi Yetti, Febri (CV. Ulil Albab Corp, 2024)
This research discusses Islamic culture. Previously, Islam did not immediately spread to various regions by itself, but rather through a very long process. This process will later become the path for the development of Islamic culture in various regions and countries throughout the world. The background for researchers to conduct this research is based on our interest in Islamic culture from the past to the present. The research method used is a descriptive analysis research method with techniques for collecting data through literature study by collecting information from various books and journals. The results of this research show that the history of Islamic culture is a science that studies the work, tastes and creations of Islamic people in the past in social, cultural, economic, political and other forms of life. The principles of Islamic culture refer to the source of Islamic teachings, namely respecting reason, motivating to demand and develop knowledge, avoiding blind beliefs, and not causing destruction. Key words: history, culture, Islam